Development of Optical Transducer on Fabrics for The Application of Liquid Clustering Using Reflectance Spectroscopy - Viona Hazar Briliana; Totok Mujiono (JAREE (Journal on Advanced Research in Electrical Engineering), 2021)
Recently, usage of fabrics as wearable device, along with their applications are increasing, one example being the detection of bio-analyzes such as blood or sweat. One method used to observe the properties of the material of a fabric is to use the Refcletance Spectroscopy, in which excitation of monochromatic light with a specific wavelength is given to a fabrics. Intensity value is then processed using the PCA method in order to obtain the pattern of the difference between each substrate. The proposed transducer optic system consists of 405nm blueviolet laser as the light source, biconvex lens, Adafruit AS7262 light detector, and Arduino. This system can only detect the difference in substrate content from the occurring light scatter. This system can be applied to various kinds of fabric wearable material with differing scatter intensity values depending on the kind of fabrics. Softer kind of fabric is proposed as material for the wearable device because it gives a high scatter intensity value and constant values in every repetation which results in better data reading.Keywords: clustering, optical, reflectance, spectroscopy, transducer, wearable.